Usability Test of DSpace on Nepalese Librarians - Nyaichyai, Lila (Access: An International Journal of Nepal Library Association, 2023)
In Nepal, the use of DSpace is increasing for building digital institutional repositories; however, its usability for Nepalese librarians was yet to be evaluated. The usability test of DSpace on Nepalese librarians assisted in evaluating DSpace from their perspective and experience. This study aimed to assess the usability of DSpace on them, examine usability factors, and identify required intervention on DSpace and the skill of Nepalese librarians to increase usability of DSpace. The study also identified the impact of training on the usability of DSpace. The pre-test questionnaire and post-test questionnaire were applied to assess the impact of training. The training on DSpace increased usability significantly (p-value = 0.0001). The task performance usability test on them resulted infectivity and efficiency of DSpace. However, there was low relation between the number of errors and time consumption during their task performance. The increased usability of DSpace on Nepalese librarians indicated the hopeful sign of increasing digital content from Nepal in coming days.